Territórios protegidos no corredor transfronteiriço entre Amapá e Guiana Francesa - Simone Dias Ferreira; José Alberto Tostes (Confins)
The state of Amapá is a federative unit of Brazil, it has a large part of its territory governed by rules for the protection of natural resources, in such a way that it directly interferes in public policies in the cross-border region with French Guiana, French Department in South America. In this way, the study addresses the issue of land situation and the condition on the border between Amapá and French Guiana. The objective of the study was to analyze the characteristics of territorial management at the border, the environmental protection rules, the dynamics and confrontations of strategic actions. The methodological actions were based on data collection, biographical and documentary research techniques with a qualitative research approach. The results obtained identified the complex diversity of interests that affect the territory with the administrative overlap of the territorial management of the federal entity that holds the largest area in hectares of Amapá land, configured as protected areas. Territorial management is conflicting, caused by the inconsistency between the purposes of creating protected areas and the potential inherent in the cross-border corridor, and the third aspect, are the challenges of confrontation in the territorial organization of Amapá that are directly related to the process os strengthening governance, as competent institutions such as communities living in the vicinity of protected areas, do not participate much in improving the indicators of sustainability and social inclusion, and can provide the development inducing the conservation of natural and cultural resources of conservation units for full use in the state of Amapá. The conclusion of the article is that the territorial area where the biodiversity corridor is inserted is the same area where the Amapá cities that integrate the cross-border corridor are inserted, but the plans are not integrated, thus generating fragmented institutional actions.